(untitled) (Romanian Biotechnological Letters, 2024)
The soils of the green areas located near the traffic corridors accumulate different pollutants, especially heavy metals, which have an important impact on the microbial decomposition processes. The extracellular enzymes can be used as an indicator of the metabolic activity of the microorganism communities. Four extracellular enzymes - α and β glucosidase, alkaline phosphatase and alanine aminopeptidase - were assessed in green areas close to the traffic zones in several urban, peri-urban and rural localities in Romania. The data showed that the highest values of enzymatic activities were registered in rural areas. At the same time, the spatial dynamics of the studied enzymes revealed an important variability between the three types of sampled areas, without a clear pattern of their distribution.